The Effect Of Sharia Financial Inclusion And Sharia Financial Literature On Financial Behavior Â¬(Case Study on Islamic Boarding School Community in Banten Province) - Fachri, Saeful; Kahpi, Heri Sapari (PINISI Discretion Review, 2021)
Financial behavior is a must-have ability that aims to manage and use financial resources in making financial decisions. Financial inclusion and Islamic financial literacy are variables that are thought to influence the financial behavior of Islamic boarding schools in Banten Province. This research leads to the type of causality research and quantitative research. Where based on the results of data analysis, the research results empirically prove that there is a positive and significant influence of the individual financial inclusion variable on financial behavior and proves that there is a positive and significant influence of the Islamic financial literacy variable on the financial behavior of Islamic boarding schools in BantenProvince.